Biomechanical in vitro evaluation of the complete porcine spine in comparison with data of the human spine - Wilke, Hans-Joachim (Springer-Verlag, 2011)
The purpose of this study was to provide quantitative biomechanical properties of the whole porcine spine and compare them with data from the literature on the human spine. Complete spines were sectioned into single joint segments and tested in a spine tester with pure moments in the three main anatomical planes. Range of motion, neutral zone and stiffness parameters of the spine were determined in flexion/extension, right/left lateral bending and left/right axial rotation. Comparison with data of the human spine reported in the literature showed that certain regions of the porcine spine exhibit greater similarities than others. The cervical area of C1–C2 and the upper and middle thoracic sections exhibited the most similarities. The lower thoracic and the lumbar area are qualitatively similar to the human spine. The remaining cervical section from C3 to C7 appears to be less suitable as a model. Based on the biomechanical similarities of certain regions of the porcine and human spines demonstrated by this study results, it appears that the use of the porcine spine could be an alternative to human specimens in the field of in vitro research. However, it has to be emphasized that the porcine spine is not a suitable biomechanics surrogate for all regions of the human spinal column, and it should be carefully considered whether other specimens, for example from the calf or sheep spine, represent a better alternative for a specific scientific question. It should be noted that compared with human specimens each animal model always only represents a compromise.